2020
DOI: 10.3390/nano11010007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins as a Key Piece in Nanostructured Materials: Quantitation and Remediation of Pollutants

Abstract: Separation and pre-concentration of trace pollutants from their matrix by reversible formation of inclusion complexes has turned into a widely studied field, especially for the benefits provided to different areas. Cyclodextrins are non-toxic oligosaccharides that are well known for their host–guest chemistry, low prices, and negligible environmental impact. Therefore, they have been widely used as chiral selectors and delivery systems in the pharmaceutical and food industry over time. However, their use for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Since cyclodextrins can self-adapt their structure to the structure of the adsorbed pollutant by reorganization, they are an ideal example of a material with great potential to remove organic contaminants from the environment. Adsorption of organic pollutants as a means of removal was tested on cyclodextrin-based [121]. Previous work has shown that cyclodextrins help remove endocrine-active compounds, pharmaceuticals, and other organic compounds [122,123].…”
Section: Removal Of Organic Compoundsmentioning
confidence: 99%
“…Since cyclodextrins can self-adapt their structure to the structure of the adsorbed pollutant by reorganization, they are an ideal example of a material with great potential to remove organic contaminants from the environment. Adsorption of organic pollutants as a means of removal was tested on cyclodextrin-based [121]. Previous work has shown that cyclodextrins help remove endocrine-active compounds, pharmaceuticals, and other organic compounds [122,123].…”
Section: Removal Of Organic Compoundsmentioning
confidence: 99%
“…We recently tested native cyclodextrins (CDs) as solubility promoters for the two precursors [ 21 ]; the increase in the solubility of the inorganic moiety (PbI 2 ) was detected via UV-Vis absorption, whereas NMR was chosen for studying the interactions involving MAI and the macrocycles with different size cavities (α, β and γ in ascending order). Cyclodextrins were chosen because of their well-known ability to establish host-guest interactions with organic molecules: the guest, according to its functional groups, interacts with the hydrophobic inner cavity of the CD and/or with its hydrophilic external surface, decorated by –OH groups [ 52 , 53 , 54 , 55 ].…”
Section: Bulk Perovskitesmentioning
confidence: 99%
“…On the other hand, in recent years, there has been an increasing interest of the scientific community the use of cyclodextrin (CD) with different purposes, which are natural products obtained from the enzymatic degradation of starch and therefore have a low price, negligible environmental impact and non-toxicity [14][15][16] . CDs are a family of natural torus-shaped cyclic oligosaccharides composed of 6 ( 𝛼-CD), 7 ( 𝛽-CD), and 8 ( 𝛾-CD) d -glucopyranose units linked by 𝛼− 1,4-glycosidic bonds, possessing hydrophobic inner cavities and hydrophilic outer faces.…”
Section: Introductionmentioning
confidence: 99%